Cambios conformacionales del factor de iniciación IF3 en el ribosoma durante el inicio de la traducción - Nakamoto Kuahara, Jose Alberto (2019)
Translation initiation is a crucial regulatory step in protein synthesis. Three factors (IF1, IF2 and IF3) are involved during this phase and are responsible for the selection and the quantity of the protein produced. IF3 manages the fidelity of translation and acts upon various kinetic regulatory checkpoints. Nevertheless, the relation between this function and the conformational variability of the ribosome-bound factor is unknown. We used intramolecular FRET and rapid kinetics to study the structural changes of IF3 during the formation of the initiation complex. The binding of IF1 and IF2 results in a reduced distance between IF3’s domains, while the binding of ARNt provokes an increase in the distances. The velocities of these movements were between 0.55 and 4.87 s-1. Kinetic assays in absence of the N-terminal domain resulted in a decreased binding affinity of the initiator ARNt and in a slower 70S assembly. Structural analysis correlated different IF3 conformations to the directionality of the changes determined by the kinetics data. Here we stablished a conjunct model of conformation changes of IF3 in the intermediaries of the initiation complex from the combination of kinetic and structural analysis.